Prevalence and Factors Associated with Vitamin D Deficiency and Hyperparathyroidism in HIV-Infected Patients Treated in Barcelona. (12th July 2012) - Lerma, Elisabet; Molas, M. Ema; Montero, M. Milagro; Guelar, Ana; González, Alicia; Villar, Judith; Diez, Adolf; Knobel, Hernando
Abstract : Vitamin D deficiency is an important problem in patients with chronic conditions including those with human immunodeficiency virus (HIV) infection. The aim of this cross-sectional study was to identify the prevalence and factors associated with vitamin D deficiency and hyperparathyroidism in HIV patients attended in Barcelona. Cholecalciferol (25OH vitamin D3) and PTH levels were measured. Vitamin D insufficiency was defined as 25(OH) D < 20 ng/mL and deficiency as <12 ng/mL. Hyperparathyroidism was defined as PTH levels >65 pg/mL. Cases with chronic kidney failure, liver disease, treatments or conditions potentially affecting bone metabolism were excluded. Among the 566 patients included, 56.4% were exposed to tenofovir. Vitamin D insufficiency was found in 71.2% and 39.6% of those had deficiency. PTH was measured in 228 subjects, and 86 of them (37.7%) showed high levels. Adjusted predictors of vitamin D deficiency were nonwhite race and psychiatric comorbidity, while lipoatrophy was a protective factor. Independent risk factors of hyperparathyroidism were vitamin D < 12 ng/mL (OR: 2.14, CI 95%: 1.19–3.82, P : 0.01) and tenofovir exposure (OR: 3.55, CI 95%: 1.62–7.7, P : 0.002). High prevalence of vitamin deficiency and hyperparathyroidism was found in an area with high annual solar exposure.